Química, farmacologia e etnobotânica de Anredera cordifolia (Basellaceae): fatores de influência sobre os compostos fenólicos e atividade antioxidante - Alba, Thainara Marcotto (2019)
Humanity over time has made use of medicinal plants to cure diseases and illnesses, they have contributed to people having access to primary health care for a long period. A way that the population uses as medicinal plants conducts research with their pharmacological potential. Medicinal plants synthesize various secondary metabolites and these have different biological functions as protection against pathogens and herbivores. No natural environments such as plants are subject to abiotic and biological influences, resulting in adaptations at different times and temperature variations. Research and investigation are increasingly needed to evaluate the conditions of cultivation, the time and place of collection of medicinal plants and how they react to environmental changes. Anredera cordifolia is widely used as medication for inflammation, diabetes, hypertension and has actions against important microorganisms. It has proven pharmacological action and several classes of metabolites such as phenolic compounds, flavonoids, which are the antioxidant activities. Considering its medicinal importance, we study this species through a comprehensive review of its botanical, pharmacological and chemical aspects, constituting the first chapter of this dissertation. We found that A. cordifolia presents as a plant considered invasive in some regions, but with medicinal and food use in others. Notable studies with this species in Indonesia and region, including the development of topics with antiinflammatory action. Numerous papers proven by their pharmacological actions, but few are the chemical compounds used by the species. In a second chapter of this work, we present experimental data where the phenolic compounds content and an antioxidant capacity of plant leaf extracts are adjusted according to different age groups and collection period. Young, mature and senescent leaves were analyzed in the four seasons of the year. Phenolic compounds were used by the Folin-Ciocalteu method and an antioxidant activity by the free radical 2,2-diphenyl-1-picril-hydrazyl (DPPH) method. The selected results, which conclude that for use with higher content of phenolic compounds, should be used as young leaves collected in winter. And to use the measures with the highest antioxidant action, select the young leaves collected in the fall.